A connection between interior grabens in the Wilkes Subglacial Basin and the continental shelf region of East Antarctica? - Fausto Ferraccioli; Egidio Armadillo; Duncan Young; Jamin Greenbaum; Antonia Ruppel; Andreas Läufer; Donald Blankenship; Martin Siegert (2018)
The Wilkes Subglacial Basin (WSB) is one of the most extensive tectonic elements in East Antarctica. It stretches for 1,400 km from the George V Coast towards South Pole and may link to the Pensacola-Pole Subglacial Basin further south, which in turn connects to the Jurassic Weddell Sea Rift. The origin of the WSB has been a matter of considerable debate for over three decades. Early models favoured an extensional origin and a several km thick sedimentary infill of Mesozoic to Cenozoic age within the basin. In contrast, later models suggested that the WSB formed in response to Cenozoic lithospheric flexure induced by the uplift of the Transantarctic Mountains (TAM), and contains no significant post-Jurassic sedimentary infill. Detailed 3D process-oriented models quantifying the relative roles of possible extension, erosion and flexure in the WSB induced by TAM uplift remain to be more fully developed. Irrespective of the uncertainties surrounding the tectonic origin of the broader WSB, aerogeophysical ob- servations collected as part of the WISE-ISODYN project clearly indicate that the northern WSB adjacent to the Northern Victoria Land (NVL) segment on the TAM contains deep structurally controlled sub-basins, namely the Eastern, Central and Western basins. 2D magnetic models (Ferraccioli et al., 2009, Tectonophysics) suggest that the Central basins represent post-Jurassic grabens linked to as yet un-quantified amounts of upper crustal brittle extension. Additionally, the characteristic mesa-like subglacial topography within the inferred grabens, likely reflects Beacon sediments intruded by Jurassic sills, forming part of the Ferrar Large Igneous Province. Airborne gravity data suggest however that there is no significant Moho upwarp beneath the upper crustal grabens, in contrast e.g. to crustal-scale rifts in West Antarctica. Airborne radar observations collected as part of the more recent ICECAP surveys suggest that similar graben-like features may also underlie the eastern and western Cook ice streams at the ...